(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2025)
This article analyzes the principles, technologies, and professional workflows involved in the development of drawings and graphics in vector and raster formats. Drawing on a review of literature, software comparisons, and case studies from engineering, architecture, and design, the study highlights the respective advantages, limitations, and integration strategies for both paradigms. Key findings reveal that hybrid workflows—combining the precision of vectors with the richness of rasters—enable superior results in technical documentation, visualization, and digital communication. The article concludes by emphasizing the importance of digital literacy, standards adoption, and software interoperability for the efficient and innovative use of vector and raster graphics in contemporary practice.